Pemberdayaan Desa Tambakcemandi Menuju Desa Tangguh Bencana melalui Literasi Digital Pesisir - Muhammad Hilmy Aziz; Dwi Prasetyo (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2026)
Coastal villages are highly vulnerable to hydrometeorological and geological disasters, including tidal flooding and tsunamis. This study aims to analyze the role of strengthening digital literacy in establishing Tambak Cemandi Village as a disaster-resilient village. Participatory Action Research (PAR) and qualitative case study approaches were used to actively engage the community, particularly fishermen, in every stage of the activity. Data collection techniques included Focus Group Discussions (FGDs), participant observation, and digital content analysis. The results indicate that digital literacy can increase the speed and accuracy of disaster information dissemination, optimize community-based early warning systems, and build community adaptive capacity. The synergy between local knowledge, information technology, and cross-sector collaboration has proven to be an effective strategy in creating a disaster-resilient coastal village. These findings recommend the development of a sustainable digital literacy program as an integral part of disaster mitigation strategies in coastal areas.